PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN STUDI KASUS: CV HOLIYEAY INDONESIA DALAM INDUSTRI PARFUM - Budi Setiawan, Fauzi; Jahani, Jahani; Sjaiful, Evilina (Gapenas Publisher, 2024)
The development of marketing in Indonesia from the traditional era to the digital era reflects rapid changes in technology, consumer behavior, and market demands. In the context of consumer behavior and market demands, the level of customer satisfaction is the peak of customer decisions in choosing and purchasing a product or service offered in a sustainable manner. The purpose of this study is to determine the influence of product quality (X1), Price (X2) and Service Quality (X3) on the variables of Customer Satisfaction (Y). The number of respondents was taken using the Slovin Formula. The sample in this study amounted to 133 respondents. The technical data analysis in this study is using a statistical methodology with the help of SPSS for Windos version 29.0. Based on the results of the above data analysis, it was obtained that the Product Quality Variable (X1) had a partially significant effect on the Customer Satisfaction variable with a significance value of <0.01 < 0.05, the Price variable (X2) had a partially significant effect on the Customer Satisfaction variable with a significance value of <0.01 < 0.05, the Service Quality Variable (X3) had a partially significant effect on the Customer Satisfaction variable with a significance value of <0.01 < 0.05, the Product Quality Variable (X1) and the Price variable (X2) have a significant effect simultaneously on the Customer Satisfaction variable with a significance value of <0.01 < 0.05, the Product Quality Variable (X1) and the Service Quality Variable (Y) have a significant simultaneous effect on the Customer Satisfaction variable with a significance value of <0.01 < 0.05, then the alternative hypothesis (H5) is accepted. The Price Variable (X2) and Service Quality (X3) had a significant effect simultaneously on the Customer Satisfaction variable with a significance value of <0.01 < 0.05. The Product Quality variable (X1), Price Variable (X2) and Service Quality variable (X3) had a significant simultaneous significant effect on the Customer Satisfaction variable with a significance value of <0.01 < 0.05 and the level of influence of the significance of the independent variables X1, X2, and X3 on Y was 0.723 or 72.30%. It can be said that this influence is a very strong influence